6t+4u+1+9u=

Simple and best practice solution for 6t+4u+1+9u= equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 6t+4u+1+9u= equation:


Simplifying
6t + 4u + 1 + 9u = 0

Reorder the terms:
1 + 6t + 4u + 9u = 0

Combine like terms: 4u + 9u = 13u
1 + 6t + 13u = 0

Solving
1 + 6t + 13u = 0

Solving for variable 't'.

Move all terms containing t to the left, all other terms to the right.

Add '-1' to each side of the equation.
1 + 6t + -1 + 13u = 0 + -1

Reorder the terms:
1 + -1 + 6t + 13u = 0 + -1

Combine like terms: 1 + -1 = 0
0 + 6t + 13u = 0 + -1
6t + 13u = 0 + -1

Combine like terms: 0 + -1 = -1
6t + 13u = -1

Add '-13u' to each side of the equation.
6t + 13u + -13u = -1 + -13u

Combine like terms: 13u + -13u = 0
6t + 0 = -1 + -13u
6t = -1 + -13u

Divide each side by '6'.
t = -0.1666666667 + -2.166666667u

Simplifying
t = -0.1666666667 + -2.166666667u

See similar equations:

| 273+286+n=943 | | 4x^2-4x+7=6 | | 6x^2+43x-15= | | 7+u+9t+5u= | | 2sinx+3cosx=4x | | 9h=7h | | 6x+10=64-3x | | 0=4x^3-12x^2-24x+32 | | .04x^2-4x=0 | | 2[5+2(9-4)]= | | 12+8x=4x+20 | | 9u+4+8t+3u= | | 5-2x+2=15 | | 2y=6-2.5x | | 9xsquared+16x=41 | | 9x+2=-5 | | 3x^2-12x-5=-6x^2 | | 6=2y+2.5x | | 6=2.5x+2y | | -9x+2=5 | | 5=3x-2+4x+1 | | 8x-(22x+7)=5x(2x-2)+8 | | 7x+5y-5(4x-7y)= | | B=(r+k)f | | y=15-10 | | 9y-8y-3=7 | | -81=5x-2(-2x+9) | | 3p^5=12 | | 2x^2-7x-1=3 | | 2(-4+3y)+6y=5 | | 2x+14+12y= | | x+(x*.15)=40 |

Equations solver categories